Textbook of diabetes and pregnancy - Hod, Moshe; Jovanovic, Lois; Di Renzo, Gian Carlo; De Leiva, Alberto; Langer, Oded (Series in maternal-fetal medicine., 2008)
Babies of women with diabetes are nearly five times more likely to be stillborn; are almost three times more likely to die in the first three months; and twice as many are born with major congenital malformations. The incidence is high--somewhere between 3 and 7 per cent of all pregnant women in the USA have diabetes--and rising; the condition is often complicated by other risk-factors such as obesity and heart disease. This book gives a comprehensive review of the epidemiology, science and clinical management of gestation diabetes. The book provides a comprehensive, authoritative, international view of these difficult pregnancies and will be invaluable to maternal-fetal medicine specialists, diabetologists, neonatologists, and basic scientists working in the field.